2014
DOI: 10.1111/jcmm.12221
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion or TWEAK blocking antibody administration reduce atherosclerosis and enhance plaque stability in mice

Abstract: Clinical complications associated with atherosclerotic plaques arise from luminal obstruction due to plaque growth or destabilization leading to rupture. Tumour necrosis factor ligand superfamily member 12 (TNFSF12) also known as TNF-related weak inducer of apoptosis (TWEAK) is a proinflammatory cytokine that participates in atherosclerotic plaque development, but its role in plaque stability remains unclear. Using two different approaches, genetic deletion of TNFSF12 and treatment with a TWEAK blocking mAb in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 36 publications
0
48
0
4
Order By: Relevance
“…The effects of the TWEAK/Fn14 axis on monocytes/macrophages have been supported by several studies (47)(48)(49). By inhibiting the biological function of TWEAK at Fn14 with Fn14-Fc, a study by Schapira et al (47) demonstrated that TWEAK and Fn14 interactions may alter macrophage trafficking and increase lipid uptake of macrophages.…”
Section: Inf Lammatory Response Of Monocytes/macrophagesmentioning
confidence: 65%
See 1 more Smart Citation
“…The effects of the TWEAK/Fn14 axis on monocytes/macrophages have been supported by several studies (47)(48)(49). By inhibiting the biological function of TWEAK at Fn14 with Fn14-Fc, a study by Schapira et al (47) demonstrated that TWEAK and Fn14 interactions may alter macrophage trafficking and increase lipid uptake of macrophages.…”
Section: Inf Lammatory Response Of Monocytes/macrophagesmentioning
confidence: 65%
“…Additionally, TWEAK was revealed to induce various proinflammatory mediators of atherogenesis, such as IL-6, MCP-1 and IL-8 in activated monocytes (48). There is also evidence that TWEAK is able to enhance MMP-9 and -2 protease activity in apolipoprotein E knockout mice (49).…”
Section: Inf Lammatory Response Of Monocytes/macrophagesmentioning
confidence: 99%
“…In vitro experiments have demonstrated that TWEAK increases adhesion molecules expression in endothelial cells [34]. TWEAK/Fn14 interaction also augments chemokines expression and secretion by both vascular smooth muscle cells (VSMCs) and macrophages [3,5]. In addition, TWEAK also induces metalloproteinase 3 and 9 activity in both VSMCs and macrophages, favoring plaque instability [5,6].…”
Section: Discussionmentioning
confidence: 96%
“…TWEAK/Fn14 interaction also augments chemokines expression and secretion by both vascular smooth muscle cells (VSMCs) and macrophages [3,5]. In addition, TWEAK also induces metalloproteinase 3 and 9 activity in both VSMCs and macrophages, favoring plaque instability [5,6]. On the other hand, in vivo experiments have demonstrated that TWEAK participates in development, progression and ultimate rupture of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation